Targeting RAGE prevents muscle wasting and prolongs survival in cancer cachexia. Issue 4 (11th March 2020) - Chiappalupi, Sara; Sorci, Guglielmo; Vukasinovic, Aleksandra; Salvadori, Laura; Sagheddu, Roberta; Coletti, Dario; Renga, Giorgia; Romani, Luigina; Donato, Rosario; Riuzzi, Francesca
Abstract: Background: Cachexia, a multifactorial syndrome affecting more than 50% of patients with advanced cancer and responsible for ~20% of cancer‐associated deaths, is still a poorly understood process without a standard cure available. Skeletal muscle atrophy caused by systemic inflammation is a major clinical feature of cachexia, leading to weight loss, dampening patients' quality of life, and reducing patients' response to anticancer therapy. RAGE (receptor for advanced glycation end‐products) is a multiligand receptor of the immunoglobulin superfamily and a mediator of muscle regeneration, inflammation, and cancer. Methods: By using murine models consisting in the injection of colon 26 murine adenocarcinoma (C26‐ADK) or Lewis lung carcinoma (LLC) cells in BALB/c and C57BL/6 or Ager −/− (RAGE‐null) mice, respectively, we investigated the involvement of RAGE signalling in the main features of cancer cachexia, including the inflammatory state. In vitro experiments were performed using myotubes derived from C2C12 myoblasts or primary myoblasts isolated from C57BL/6 wild type and Ager −/− mice treated with the RAGE ligand, S100B (S100 calcium‐binding protein B), TNF (tumor necrosis factor)α±IFN (interferon) γ, and tumour cell‐ or masses‐conditioned media to analyse hallmarks of muscle atrophy. Finally, muscles of wild type and Ager −/− mice were injected with TNFα/IFNγ or S100B in a tumour‐free environment. Results: We demonstrate that RAGE is determinant to activate signalling pathways leading to muscle protein degradation in the presence of proinflammatory cytokines and/or tumour‐derived cachexia‐inducing factors. We identify the RAGE ligand, S100B, as a novel factor able to induce muscle atrophy per se via a p38 MAPK (p38 mitogen‐activated protein kinase)/myogenin axis and STAT3 (signal transducer and activator of transcription 3)‐dependent MyoD (myoblast determination protein 1) degradation. Lastly, we found that in cancer conditions, an increase in serum levels of tumour‐derived S100B and HMGB1 (high mobility group box 1) occurs leading to chronic activation/overexpression of RAGE, which induces hallmarks of cancer cachexia (i.e. muscle wasting, systemic inflammation, and release of tumour‐derived pro‐cachectic factors). Absence of RAGE in mice translates into reduced serum levels of cachexia‐inducing factors, delayed loss of muscle mass and strength, reduced tumour progression, and increased survival. Conclusions: RAGE is a molecular determinant in inducing the hallmarks of cancer cachexia, and molecular targeting of RAGE might represent a therapeutic strategy to prevent or counteract the cachectic syndrome.